The relative age effect in body size and success of world-class handball players - Massuca, L. M. (EHF Scientific Conference 18.-19.11.2011, Wien, Österreich, 2011)
To investigate the chronological age effect, of world-class handball players (WCHB), in body size and in success during handball (HB) competition, a sample of 939 WCHB was studied. The chronological age, height and weight, body mass index and optimal weight were studied. Age differences can result in significant variance in body size and success. Also height and weight seems relevant to be successful in world-class HB.